Pengaruh Sampah Rumah Tangga Terhadap Kulitas pH Air Tempat Pembuangan Akhir TPA Air Sebakul Kelurahan Sukarami Kecamatan Selebar Kota Bengkulu - auliya, anisa; Walid, Ahmad; ikhsan, adli (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
Abstract. Garbage is a consequence of human activity. Every human activity definitely produces waste or garbage. Of the many human activities, it is the most dangerous household waste. Although we do not live in coastal areas and many industrial wastes that are not processed can also harm the sea water but see the many people of Indonesia with unprocessed household waste and produced every day. This research uses an experimental or direct observation method that aims to determine the influence of household samaph to the quality of water pH at the end of the LANDFILL. From the results of the experiments conducted for 1 day and took 5 sources of both water source and liquid waste formed turns the pH quality of water that formed an average of about 80% have a charactercytic water that is acidic. As well as having other properties such as black and dark waste color and unpleasant Aroma caused.